Experimental Verification of the Steering Performance of All-Hydraulic Crawler Chassis - LV, Xiaolian; LV, Xiaorong; SHI, Xiaojie; WANG, Tingyu (Engineering Transactions, 2018)
The force conditions in the steering system of the chassis under different conditions are analyzed theoretically for the independently designed and developed all-hydraulic crawler chassis. Using the multi-body dynamic simulation software RecurDyn, the chassis steering performance on sandy loam and clay pavements, and the steering performance under different steering radiuses on the sandy loam pavement are simulated and analysed dynamically respectively. The steering resistance moment is studied when the pavement conditions and steering radius are different. This research selects inside and outside crawler slip ratio as an index, and road conditions, speed and steering radius as factors to test the steering performance of all-hydraulic crawler chassis under different operating conditions. It is observed from the simulation results that during the pivot steering on the sandy loam, the drive torque and braking torque of the driving wheel are larger than on the clay ground. With the decrease of the steering radius, the torques of the left and right driving wheel are both gradually increasing. In the same steering radius, the torque of the outside driving wheel is larger than that of the inside driving wheel. The simulation results are consistent with the theoretical analysis results. In the steering performance test, the factors influencing the slippage rate on both sides of the crawler are such that the influence of the steering radius is greater than that pf the pavement condition and the pavement condition influence is greater than that of the speed. Among them, the steering radius has a significant influence on the slip ratio of the inside crawler, and an extremely significant influence on the slip ratio of the outside crawler. This research can provide a certain theoretical basis and technical reference for the development of hydraulic crawler chassis and optimization of the steering system.